The innovation of intelligent system e-consultant learning to improve student mindset of vocational education in the disruptive Era 4.0 - R. Putra, A. B. N.; Insani, N.; Winarno, A.; Puspitasari, P.; Kiong, T. T.; Habibi, M. A.; Tuwoso, Tuwoso; Subandi, M. S. (2020)
In this disruptive 4.0 era, the student mindset has decreased significantly. This mindset is related to the ability to become a professional teacher. This is due to the very limited number of innovations in the form of an expert system as a means of direct consultation regarding vocational education. This study aims to: 1) analyze the factors that influence the student mindset of vocational education in the disruptive era; 2) developing the innovation of intelligent econsultant learning system, and 3) testing the level of attractiveness of the innovation of intelligent system e-consultant learning. The method used in this study is the research and development (R&D) method. The informants in this study were all vocational education students at State Universities in East Java. Expert testing was carried out by experts in online learning media and material experts in the field of vocational education. The results of this study include: 1) the factors that affect the student mindset of vocational education in the disruptive era, namely internal factors (problems manipulate abilities, education perceptions, thinking tenacity, social interaction, high curiosity, experiment ability, and reliable creator), and external factors (work environment, association with the society, belief systems, family relationships, and educational policies); 2) the innovation of intelligent e-consultant learning system developed has a high level of attractiveness and is well based on experts in online learning media and material experts in the field of vocational education; and 3) the product innovation of intelligent system e-consultant learning developed can be used as an alternative learning media in a disruptive era.